Effect of Blade Profile on the Performance of Wells Turbine under Unidirectional Sinusoidal and Real Sea Flow Conditions - A. Thakker; R. Abdulhadi (International Journal of Rotating Machinery)
This paper presents the effect of blade profile and rotor solidity on the performance of Wells turbine operating under unidirectional unsteady flow conditions. In the study, four kinds of blade profile were selected, that is, NACA0020, NACA0015, CA9, and HSIM 15-262123-1576. The experiments have been carried out for two solidities, σ = 0.48 and σ = 0.64, under sinusoidal and irregular unsteady flow conditions based on Irish waves (site2). As a result, it was found that the preferable rotor geometry is the one with blade profile of CA9 with solidity σ = 0.64. In addition, the effect of blade profile and rotor solidity on hysteretic characteristics of the turbine has been clarified experimentally and it was found to be in good agreement qualitatively when compared to numerical results (Setoguchi et al. (2003)).